Case Report: Eccentric purulent pericarditis treated by PTCA guidewire-based pericardiocentesis and intrapericardial alteplase - Li, Can; Qin, Chun-Chang; Jiang, Yue; Hou, Lin (Frontiers in Cardiovascular Medicine, 2025)
BackgroundPurulent pericarditis is an infectious condition characterized by purulent pericardial effusion.Case presentationIn this case report, we present a 60-year-old male admitted with intermittent chest pain and fever, ultimately diagnosed with primary purulent pericarditis. Imaging revealed an eccentric loculated pericardial effusion, posing significant challenges for conventional pericardiocentesis. In this context, we innovatively employed a percutaneous transluminal coronary angioplasty (PTCA) guidewire-based pericardiocentesis technique, achieving successful catheter placement followed by intrapericardial administration of 5 mg alteplase. During follow-up, the patient achieved complete clinical recovery.ConclusionsThis report introduces a PTCA guidewire-based pericardiocentesis approach, which safely addresses complex eccentric loculated pericardial effusions. Combined with low-dose intrapericardial alteplase, drainage efficacy was enhanced, pericardial adhesions were reduced, and invasive pericardiectomy could be avoided. This minimally invasive technique provides a viable alternative to surgery for high-risk patients.